Synthesis of silver nanoparticles from pericarp of Ziziphus jujuba Mill. and their in vitro antimicrobial activity (Bangladesh Journal of Botany, 2022)
Silver nanoparticles (AgNPs) used in this study were prepared from Ziziphus jujuba Mill. aqueous pericarp extract. Potent antibacterial activity was recorded from AgNPs–Z. jujuba pericarp against P. Pseudomonas aeruginosa > K. Klebsiella pneumoniae > M. Micrococcus luteus > S. Staphylococcus aureus > P. Proteus mirabilis > S. Shigella flexneri. Less antifungal activity was found against phytopathogenic fungi with inhibition efficacy of P. Penicillium expansum > M. Macrophomina phaseolina > A. Alternaria alternata > D. Drechslera halodes, F. Fusarium oxysporum f. sp. lycopersici. UV-Vis spectral analysis of formed AgNPs– Z. jujuba was recorded at 450 nm and three characteristic diffraction peaks observed at 2Φ =38.235, 43.95 and 64.42. FTIR patterns were located in the region of 4000–400 cm−1 and AgNPs particle size were noticed in between 20 and 71 nm with spherical shape embedded in bio-materials. These findings indicate that AgNPs–Z. jujuba pericarp aqueous extract could be utilized to control various bacterial infections to human and as well as against phytopathogenic fungi.Bangladesh J. Bot. 51(2): 305-312, 2022 (June)